Method for introducing TBA cation into layered oxide, combination of nonaqueous solvent and TBA cation used in the method, and oxide nanosheet
By introducing TBA cations into layered oxides using a non-aqueous solvent mixture, the method overcomes the limitations of aqueous solvent-based synthesis, enabling the production of oxide nanosheets with uniform properties and allowing for the creation of novel inorganic-organic composite structures.
Patent Information
- Application Number
- JP2023161557
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
Existing methods for synthesizing oxide nanosheets are limited by the use of aqueous solvents, which restricts the application of unstable layered substances and requires multi-step processes, making it difficult to achieve uniform thickness and size control.
Introducing TBA cations into layered oxides using a non-aqueous mixed solvent composed of acetonitrile and methanol, allowing for intercalation and subsequent synthesis of oxide nanosheets in a non-aqueous solvent environment.
This method enables the synthesis of oxide nanosheets without water, allowing for the incorporation of organic molecules unstable in water and achieving uniform dispersion of inorganic-organic composites, thus facilitating the formation of novel structures and realizing one-pot synthesis in non-aqueous solvents.
Smart Images

Figure 2025052707000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for introducing TBA cations into layered oxides, which enables nanosheets to be obtained from layered substances in non-aqueous solvents, a combination of non-aqueous solvents and TBA cations used in the method, and oxide nanosheets. [Background technology]
[0002] Nanosheets synthesized by exfoliating layered compounds have a very large aspect ratio and high two-dimensional anisotropy, and are therefore attracting attention as building blocks for forming various functional structures. Nanosheets have been synthesized from various elemental species, and are known to be used to take advantage of the properties derived from the elements, such as electrical conductivity and semiconducting properties. Methods for synthesizing nanosheets from layered compounds can be broadly divided into physical and chemical methods. The physical method is a method in which the layered compound is irradiated with ultrasound in a solution, causing the layered compound to be crushed and peeled off. This method changes the degree of dispersion depending on the compatibility between the nanosheet and the solvent, making it possible to synthesize large quantities, but it is difficult to synthesize nanosheets with uniform thickness and size. The chemical method allows exfoliation by intercalating molecules or ions that act as exfoliation inducers between the layers of the layered compound, weakening the host-guest interaction. This method is excellent for synthesizing single-layered nanosheets, and is therefore often used when using them as building blocks.
[0003] Oxide nanosheets are conductive and have semiconducting properties, so there has been much research being done on their use as photocatalysts and electrode materials. Tetrabutylammonium hydroxide (TBAOH), a quaternary ammonium, is used to peel off layered oxides. TBAOH ionized in an aqueous solution + (also called "TBA cation") intercalates through a cation exchange reaction with the interlayer protons, weakening the host-guest interaction through steric hindrance. It is also known that, as a preliminary step to peeling, water enters the gap between the layers due to the osmotic pressure between the layers and the aqueous solution, causing swelling.
[0004] Reports of the synthesis of oxide nanosheets in organic solvents include a method in which nanosheets produced in water are recovered and redispersed in an organic solvent, and a method in which the surface of the host layer is hydrophobically modified to introduce a solvent and synthesize organically modified nanosheets (Non-Patent Documents 1, 2, Patent Documents 1-3).
[0005] Non-Patent Document 1 reports that a nanosheet colloid is obtained by re-stacking a titanate nanosheet colloid obtained by peeling in an aqueous solvent and dispersing it in a non-aqueous solvent. Non-Patent Document 2 reports that a nanosheet colloid is obtained by reacting a layered oxide with a long-chain alkylamine to produce an organic-inorganic composite, and then dispersing it in a non-aqueous solvent. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] W. Sugimoto, O. Terabayashi, Y. Murakami and Y. Takasu, Electrophoretic deposition of negatively charged tetratitanate nanosheets and transformation into preferentially oriented TiO2(B) film, J. Mater. Chem., 12, 3814(2002). [Non-Patent Document 2] M. Honda, Y. Oaki and H. Imai, Hydrophobic Inorganic-Organic Composite Nanosheets Based on Monolayers of Transition Metal Oxides, Chem. Mater., 26, 3579(2014). [Patent documents]
[0007] [Patent Document 1] JP 2008-174431 A Summary of the Invention [Problem to be solved by the invention]
[0008] In the above-mentioned conventional techniques, the synthesis of nanosheets is generally carried out in an aqueous solution, and the formation of functional structures is also limited by the solvent water. For example, reactions that use hydrolysis cannot be used in reactions to modify nanosheets, and it is difficult to remove the effects of electrolysis of water when creating electrophoretic deposition films. In addition, since aqueous solvents are used in the synthesis process, layered substances and intercurants that are unstable in water, such as those that dissolve in water, cannot be applied. If nanosheets can be created in organic solvents, these problems will be solved and inorganic-organic composites will also be able to be uniformly dispersed, so the formation of structures different from those used in the past can be expected. In addition, in conventional techniques, many processes require both aqueous and organic solvents, and one-pot synthesis using only non-aqueous solvents has not been realized.
[0009] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a method for introducing TBA cations into layered oxides, which enables nanosheets to be obtained from raw materials in a non-aqueous solvent, a combination of non-aqueous solvent and TBA cation used in the method, and an oxide nanosheet. [Means for solving the problem]
[0010] (1) The method for introducing TBA cations into a layered oxide according to the present invention is characterized in that it involves intercalating a quaternary ammonium cation into the layered oxide in a non-aqueous mixed solvent consisting of acetonitrile and methanol.
[0011] In the method for introducing TBA cations into a layered oxide according to the present invention, the mixed solvent preferably has a volume fraction of [acetonitrile] / [acetonitrile+methanol] in the range of 20% to 80%.
[0012] In the method of introducing TBA cations into a layered oxide according to the present invention, the layered oxide is preferably layered titanic acid.
[0013] In the method of introducing TBA cations into a layered oxide according to the present invention, one or both of the layered oxide and the quaternary ammonium cation are substances that are unstable in water.
[0014] (2) The combination of a non-aqueous solvent and a TBA cation according to the present invention is a combination used for introducing a TBA cation into a layered oxide, and is characterized in that it contains a mixed solvent of acetonitrile and methanol, and a quaternary ammonium cation.
[0015] In the combination of the non-aqueous solvent and the TBA cation according to the present invention, the mixed solvent preferably has a volume fraction of [acetonitrile] / [acetonitrile+methanol] within the range of 20% to 80%.
[0016] (3) The oxide nanosheet according to the present invention is characterized in that it is an oxide nanosheet obtained by a method including the above-mentioned method for introducing TBA cations into the layered oxide according to the present invention. Effect of the Invention
[0017] According to the method of introducing TBA cations into layered oxides according to the present invention, intercalation of quaternary ammonium cations into layered oxides can be achieved in a non-aqueous mixed solvent consisting of acetonitrile and methanol. As a result, since only a non-aqueous solvent can be used, oxide nanosheets dispersed in a non-aqueous solvent can be obtained without using water in the manufacturing process. In addition, since only a non-aqueous solvent can be used, organic molecules that are unstable in water can be composited with layered oxides, and organic molecules can be composited with layered oxides that are unstable in water.
[0018] According to the combination of the non-aqueous solvent and the TBA cation of the present invention, by using a mixed solvent composed of two kinds of non-aqueous solvents, it is possible to realize the intercalation of the TBA cation, which does not proceed at all when each solvent is used alone. In addition, it is expected to be an efficient method that does not require a multi-stage reaction as in the past. As a result, it is also possible to uniformly disperse the inorganic-organic composite, and it is expected to form a structure different from the conventional one. In addition, it is possible to realize a one-pot synthesis using only a non-aqueous solvent.
[0019] According to the oxide nanosheet of the present invention, it is possible to provide an oxide nanosheet dispersed in a non-aqueous solvent without using water in the manufacturing process, and also to provide an oxide nanosheet obtained by an efficient method that does not require multi-stage reactions as in the conventional method. [Brief description of the drawings]
[0020] [Figure 1] X-ray diffraction patterns of the products obtained in Experiment 1. (a) to (e) are the cases where the volume fraction (φAN) of [acetonitrile] / [acetonitrile + methanol] is 0%, 25%, 50%, 75%, and 100%, respectively, and (f) is the layered titanic acid before the reaction. [Diagram 2] These are TG-DTA curves for a sample in which the precursor, acetonitrile alone, and a mixed solvent (acetonitrile-methanol) were used as the reaction solution. [Diagram 3] These are photographs of the appearance of dispersions redispersed in acetonitrile alone, with volume fractions (φAN) of 25%, 50%, and 75% (from left). [Figure 4] AFM image (A) and height profile (B) of the dispersion when a sample with a volume fraction (φAN) of 50% was redispersed in a mixed solvent (acetonitrile-methanol). [Diagram 5] 1 shows an XRD pattern of the cast film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The method for introducing TBA cations into the layered oxide according to the present invention, the combination of the non-aqueous solvent and the TBA cation used in the method, and the oxide nanosheets will be described in detail below. However, the present invention is not limited to the following description within the scope of its technical scope.
[0022] The method for introducing TBA cations into layered oxides according to the present invention is characterized in that it is a method for intercalating quaternary ammonium cations into layered oxides in a non-aqueous mixed solvent consisting of acetonitrile and methanol. In this invention, intercalation of quaternary ammonium cations into layered oxides can be realized in a non-aqueous mixed solvent consisting of acetonitrile and methanol. As a result, since only a non-aqueous solvent can be used, oxide nanosheets dispersed in a non-aqueous solvent can be obtained without using water in the manufacturing process. In addition, since only a non-aqueous solvent can be used, organic molecules that are unstable in water can be composited to layered oxides, and organic molecules can be composited to layered oxides that are unstable in water.
[0023] The combination of non-aqueous solvent and TBA cation according to the present invention is a combination used for introducing TBA cation into layered oxide, and is characterized by including a mixed solvent of acetonitrile and methanol, and a quaternary ammonium cation. In this invention, by using a mixed solvent composed of two non-aqueous solvents, intercalation of TBA cation that does not proceed at all when each solvent is used alone can be realized. In addition, it is expected to be an efficient method that does not require multi-stage reactions as in the past. As a result, it is also possible to uniformly disperse inorganic-organic composites, and it is expected to form a structure different from the past. In addition, one-pot synthesis using only a non-aqueous solvent can be realized.
[0024] The oxide nanosheet according to the present invention is characterized in that it is an oxide nanosheet obtained by a method including the above-mentioned method for introducing TBA cations into the layered oxide according to the present invention. This invention can provide an oxide nanosheet dispersed in a non-aqueous solvent without using water in the manufacturing process. In addition, it can provide an oxide nanosheet obtained by an efficient method that does not require multi-stage reactions as in the past.
[0025] Each component will be described.
[0026] [Layered oxide] Although the layered oxide will be described below by taking layered titanic acid as an example, the layered oxide is not limited to this. Layered titanic acid can be obtained by treating a layered titanate in an acidic solution.
[0027] The method for obtaining the layered titanate is not particularly limited, but as an example, the layered titanate can be obtained by crushing titanic acid and then mixing it with an alkali metal compound (mixing process), molding the resulting mixture into tablets (molding process), subsequently carrying out the first firing (first firing process), crushing and mixing the fired tablets (crushing and mixing process), molding them again into tablets (molding process), firing them a second time (second firing process), and washing the fired product until it becomes neutral (washing process).
[0028] The alkali metal compound used in the grinding and mixing step is not particularly limited, but potassium carbonate can be mentioned. The mixing ratio of titanic acid and alkali metal compound is also not particularly limited, but for example, titanic acid:alkali metal compound=1:0.5-5. The first firing step can be a heat treatment in air or in an oxygen atmosphere or under flow, for example, at 400°C to 800°C for a predetermined time (for example, 1-12 hours). The second firing step can also be a heat treatment in air or in an oxygen atmosphere or under flow, for example, at 400°C to 800°C for a predetermined time (for example, 1-12 hours).
[0029] Layered titanic acid can be obtained by treating the obtained layered titanate in an acidic solution. For example, the treatment in an acidic solution is a treatment of immersing in an acidic solution of HCl. The obtained layered titanic acid has Lepidocrocite type TiO2 sheets stacked in layers with H+ between them.
[0030] [Non-aqueous solvent] A preferred example of the non-aqueous solvent is a non-aqueous mixed solvent consisting of acetonitrile and methanol. As will be described in the experimental examples below, the mixed solvent consisting of acetonitrile and methanol is preferably a non-aqueous mixed solvent consisting of acetonitrile and methanol, which is a solvent having a volume fraction (φ AN ) is preferably in the range of 20% to 80%, more preferably in the range of 25% to 75%. In the experimental examples described later, the intended object is achieved by using a mixed solvent, but as long as the object of the present invention can be achieved, a non-aqueous mixed solvent of a combination other than these mixed solvents or a non-aqueous single solvent may be used.
[0031] [Intercurrant] An intercalant is a compound or element that penetrates between layers of a layered oxide by intercalation. In the present invention, a quaternary ammonium cation (referred to as "TBA cation") can be preferably used as an intercalant into layered titanic acid in the experimental example described below. In the experimental example described below, TBABr salt is used as the TBA cation. In the present invention, it was found that the intercalation of TBA cation into layered titanic acid, which does not proceed at all in a single nonaqueous solvent, can be promoted in a nonaqueous mixed solvent system consisting of acetonitrile-methanol. The introduction of TBA cation into layered titanic acid can promote the peeling of layered titanic acid, which is effective in obtaining an oxide nanosheet colloid dispersed in a nonaqueous solvent.
[0032] Furthermore, when the intercalant is a substance unstable in water, intercalation into the layered oxide can be achieved in the nonaqueous solvent by using a nonaqueous solvent such as a mixed solvent of acetonitrile and methanol, which are nonaqueous solvents. As a result, organic molecules that are unstable in water can be composited into the layered oxide in the nonaqueous solvent. The above-mentioned "substance unstable in water" refers to a substance that undergoes a hydrolysis reaction and becomes a decomposition product when it comes into contact with water or an aqueous solution. Note that the layered titanic acid used in the experimental example described below does not fall under such a substance.
[0033] [Oxide nanosheets] In the present invention, the oxide nanosheet is made into a titanium oxide nanosheet from layered titanic acid as a layered oxide. The layered titanic acid obtained is reacted with alkylammonium to obtain an alkylammonium-layered titanic acid intercalation compound, and then the alkylammonium-layered titanic acid intercalation compound is shaken to obtain a titanic acid nanosheet dispersion. The obtained titanic acid nanosheet dispersion can be used to obtain a monolayer film of titanic acid nanosheets on a substrate by electrostatic interaction. As the alkylammonium, for example, tetrabutylammonium can be preferably used. As the substrate, for example, a Si substrate, a quartz substrate, etc. can be used. The formation of a titanic acid nanosheet monolayer film on a substrate can be, for example, immersing the substrate in the titanic acid nanosheet dispersion, or dropping or monolayer coating the titanic acid nanosheet dispersion onto the substrate. EXAMPLES
[0034] The present invention will now be described in more detail with reference to experimental examples.
[0035] [Experiment 1] In this experiment, the volume fraction of acetonitrile in the acetonitrile-methanol mixed solvent in which the TBA salt was dissolved was φ AN Layered titanic acid consisting of Lepidocrocite type H-TiO2 was added to the mixture (hereinafter referred to as "H-TiO2") and reacted for a certain period of time by stirring. The powder was then recovered and analyzed by X-ray diffraction (XRD).
[0036] (Preparation of layered oxide) Lepidocrocite-type H-TiO2 was synthesized by the following procedure. First, a mixture of TiO2 (anatase) powder and Cs2CO3 powder was used for synthesis by the solid-phase method. TiO2 and Cs2CO3 were mixed and formed into pellets, then placed in a platinum crucible and pre-fired for CO2 removal (800°C, 1 hour, air). The temperature in the furnace was lowered to 500°C, the sample was taken out, mixed again, formed into pellets, and then fired (800°C, 20 hours, air). The sample was similarly taken out, mixed again, formed into pellets, and then fired a second time (800°C, 20 hours, air). The temperature in the furnace was lowered to 200°C, the sample was taken out, and crushed to obtain powder of Lepidocrocite-type Cs-TiO2. This was acid-treated in 1M hydrochloric acid (24 hours). This acid treatment was repeated for three days, washed with ultrapure water, and the powder was taken out by suction filtration and dried. Thus, Lepidcrocite-type H-TiO2 (H x Ti 2-X / 4 □ X / 4 O4·H2O) was obtained.
[0037] (mixed solvent, TBA cation) A non-aqueous solvent consisting of acetonitrile and methanol was used as the mixed solvent. The volume fraction of [acetonitrile] / [acetonitrile+methanol] (φ AN ) were prepared at 0%, 25%, 50%, 75%, and 100%. TBABr salt was used as the TBA cation.
[0038] (measurement) The XRD pattern was obtained using a Rigaku X-ray diffractometer (Mini Flex600). The X-ray source used was CuKa radiation, and the tube current was set to 15 mA and the tube voltage to 40 kV. Soller slits were set at 2.5 degrees on both the irradiating and receiving sides. A glass sample plate was used as the sample plate for measurement.
[0039] The TG-DTA curves were obtained using a thermogravimetric simultaneous differential thermal analyzer (Thermo Plus: TG 8120) manufactured by Rigaku Corporation. Dry air was blown into the device at a flow rate of 0.2 L / min. Alumina oxide powder dried at 120°C was used as the reference sample, and measurements were performed in the range from room temperature to 900°C. The heating rate was 10°C / min.
[0040] The AFM images were obtained using a Bruker atomic force microscope (AFM: Multimode-SC). The Si substrate (1 cm2) was hydrophilized after removing organic matter. 2 ) was immersed in the nanosheet dispersion for 30 seconds, washed with ultrapure water, and the AFM image was observed.
[0041] [Intercalation progress depending on the mixing ratio of mixed solvents] The mixing ratio (volume fraction) of the mixed solvent was changed to evaluate the degree of intercalation depending on the degree of mixing of the solvents.
[0042] Figure 1 shows the X-ray diffraction patterns of the products obtained in Experiment 1. (a) to (e) in the figure respectively represent the volume fractions of [acetonitrile] / [acetonitrile + methanol] (φ AN ) are 0%, 25%, 50%, 75%, and 100%, and (f) is the layered titanic acid before the reaction. As can be seen from these XRD patterns, when acetonitrile and methanol were used as the reaction solution, a peak appeared (d=1.41 nm) that is thought to be due to a new stacking period. The thickness of one sheet of lepidocrocite-type TiO2 is 0.75 nm, and the expansion of the layer spacing is about 0.5 nm. When the layer spacing is calculated taking into account the expanded stacking period and the thickness of the sheet, it becomes 0.65 nm, indicating that TBA cations have been intercalated.
[0043] From these results, the XRD pattern of the product when no solvent was mixed was almost identical to that of the raw material, and it can be said that intercalation had not progressed at all (Figs. 1(a) and (e)). On the other hand, when a solvent was mixed, a new diffraction peak corresponding to the expanded stacking period between layers was confirmed on the low-angle side (Figs. 1(b) to (d)). This is thought to be due to the progress of intercalation of TBA cations. In addition, the relative intensity of the diffraction peak due to the expanded stacking period to the diffraction peak due to the stacking structure of the raw material increased with the volume fraction (φ AN ) and varies with the volume fraction (φ AN )=50%.
[0044] Figure 2 shows the TG-DTA curves of the precursor, acetonitrile alone, and a non-aqueous mixed solvent (acetonitrile-methanol) as the reaction solution. AN It can be seen that the amount of interlayer solvent is less in the case of =50%, resulting in a greater mass loss of the organic matter. A possible cause of interlayer expansion other than the intercalation of TBA cations is Me-O formation due to the appearance of Me-O bonds, but since this is a modification that decomposes with a one-stage mass loss at or below 350°C, it can be said that this is not related to the interlayer expansion in the present results. Therefore, based on the appearance of a new stacking period in the XRD pattern and the decomposition behavior of the organic matter in thermal analysis, it can be said that TBA cations can be intercalated between layers by using a non-aqueous mixed solvent as the reaction solution.
[0045] To confirm the intercalation of TBA cations, the powder sample was redispersed in acetonitrile alone. Figure 3 shows a photograph of the appearance of the dispersion liquid in which the powder sample recovered from the reaction in the mixed solvent was redispersed at 1 g / L in acetonitrile alone. In Figure 3, the powder sample used is shown from the left with a volume fraction (φ AN ) = 25%, 50%, 75%. This dispersion did not completely settle even after being left for more than a week, and the Tyndall phenomenon was confirmed when irradiated with laser light. This indicates that the TBA cationic intercalation compound is exfoliated and exists as a nanosheet colloid, and therefore exists stably.
[0046] Figure 4 shows the AFM image (A) and height profile (B) of the dispersion when redispersed as described above. Figure 5 shows the XRD pattern of the cast film. The AFM image allows observation of the form of the substance present in the dispersion. The AFM image and height profile show the presence of nanosheets with a planar size of several hundred nm and a thickness of about 1 nm. In addition, the XRD pattern of the cast film showed multiple low-angle peaks that are thought to be derived from laminates formed during the process of casting and drying the nanosheet colloid. This is thought to be because the TBA cation concentration in the solution is low, so when the nanosheets are deposited, the sheets are deposited on each other, TBA cations are present between the sheets, solvent molecules are trapped between them, or the precursor itself is dispersed. The AFM image and the appearance photographs of the cast film and the dispersion are integrated to obtain the φ AN It can be seen that in a solution in which the sample was redispersed in acetonitrile alone, the nanosheets exist as a single layer. AN = 50% of the interlayer spaces are intercalated with TBA cations, and φ AN Although there is a difference in the amount of TBA cation present in the samples with =25% and =75%, the same phenomenon occurs.
[0047] From the above, it was found that in the non-aqueous mixed solvent, a solvent environment or an interlayer environment in which TBA cations can intercalate between layers is formed.
Claims
1. A method for introducing TBA cations into a layered oxide, comprising intercalating a quaternary ammonium cation into the layered oxide in a non-aqueous mixed solvent of acetonitrile and methanol.
2. 2. The method for introducing TBA cations into a layered oxide according to claim 1, wherein the mixed solvent has a volume fraction of [acetonitrile] / [acetonitrile+methanol] in the range of 20% to 80%.
3. 2. The method for introducing TBA cations into a layered oxide according to claim 1, wherein the layered oxide is layered titanic acid.
4. 2. The method for introducing TBA cations into a layered oxide according to claim 1, wherein one or both of said layered oxide and said quaternary ammonium cations are substances unstable to water.
5. A combination of a non-aqueous solvent and a TBA cation, which is used for introducing TBA cations into a layered oxide, comprises a mixed solvent of acetonitrile and methanol, and a quaternary ammonium cation.
6. The combination of a non-aqueous solvent and a TBA cation according to claim 5, wherein the mixed solvent has a volume fraction of [acetonitrile] / [acetonitrile+methanol] in the range of 20% to 80%.
7. 5. An oxide nanosheet, characterized in that it is an oxide nanosheet obtained by a method including a method for introducing TBA cations into the layered oxide according to any one of claims 1 to 4.
Citation Information
Patent Citations
Ruthenic acid nanosheet and its producing method
JP2008174431A